2021
DOI: 10.1002/nafm.10687
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ice Angler Culling Practices on Bluegill Physiological Stress Responses and Mortality

Abstract: Decreasing bag limits is a management mechanism for enhancing size structure of Bluegill Lepomis macrochirus. However, restrictive bag limits can promote culling, where an angler returns a live fish to the water in exchange for another. Little is known about the effect of culling on ice-angled fishes.Our objective was to compare the effects of Bluegill confinement methods (reference, ice well, and bucket) and holding durations (0, 1, 2, or 5 hours) on changes in water quality parameters (dissolved oxygen, pH, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…Furthermore, one or more of the sampled tissues may have experienced “cold shock”, which is characterized as biological impairments induced by rapid decrease in water temperature (Donaldson et al, 2008). Cold shock results in a suite of physiological changes and in extreme cases, death of the organism (Donaldson et al, 2008), though mortality has rarely been reported in ice fishing studies (e.g., Grausgruber et al, 2021; Logan et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, one or more of the sampled tissues may have experienced “cold shock”, which is characterized as biological impairments induced by rapid decrease in water temperature (Donaldson et al, 2008). Cold shock results in a suite of physiological changes and in extreme cases, death of the organism (Donaldson et al, 2008), though mortality has rarely been reported in ice fishing studies (e.g., Grausgruber et al, 2021; Logan et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A potential outcome of this cooling is the slowing of key physiological processes (e.g., enzyme activity, metabolism, hormone production). Past studies on ice fishing have shown that metabolic and stress responses (e.g., glucose, lactate, cortisol) are either absent or lower in caught fish in comparison to fish sampled following fishing in warmer time periods, which has been attributed to a slowing of the enzymatic processes needed for the physiological stress response (Grausgruber et al, 2021; Logan et al, 2019; Louison, Hasler, Fenske, et al, 2017; Louison, Hasler, Raby, et al, 2017). The cooling may also contribute to behavioural and locomotory impairment that has also been noted following ice fishing (Bieber et al, 2019; LaRochelle et al, 2021; Logan et al, 2019; Louison et al, 2017a; Louison, Hasler, Raby, et al, 2017), as neuronal activity and forced swimming performance slow at cooler temperatures (Ward et al, 2002; Van den Burg et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations